EPIDEMIOLOGICAL CHARACTERISTICS AND CHILDBIRTH TRENDS IN SERBIA - Radovanovic, Snezana; Maricic, Milena; Radivojevic, Sladjana; Stanojlovic, Predrag; Simovic Šiljkovic, Divna; Mujkovic, Marija; Gazdic, Mirjana (HEALTH CARE, 2020)
Introduction/Aim: In recent decades, declines in fertility rates have been reported in almost every country in the world. The aim of the research is the analysis of epidemiological characteristics and childbirth trends in Serbia in the period 2007-2016.Methods: The study was designed as a retrospective, descriptive, epidemiological study. The research data were collected from the Health Statistical Yearbooks of the Institute of Public Health of the Republic of Serbia "Dr Milan Jovanovic Batut" in the period 2007-2016. Total fertility rates, stillbirth rates, birth rates, infant mortality rates, and preterm birth rates were used for the analysis of data, while the linear trend and regression analysis were used to analyze the trend.Results: Average rate of general fertility in Serbia in the period 2007-2016 was 1.5 children per woman.In the period 2007-2016, 660,069 births were registered in Serbia with a total of 671,715 children born, of which 4,054 were stillborn (0.6%). Two thirds (66.1%) of stillborn children were born prematurely. The number of premature births increased with maternal age. Of 667,661 live births in maternity hospitals, 924 newborns died (0.1%). In the observed period, a continuous trend of decreasing number of births was registered (y = 68,427-439.99x, R2 = 0.628), as well as the number of live births (y = 69,084-421.44x, R2 = 0.591). The trend of still birth rates showed a slight decrease (y = 6,138-0,012x, R2 = 0,016), as well as the trend of infant mortality rates (y = 1,882-50,091x, R2 = 0,683), but there came to an increase in the trend of the general fertility rate (y = 39.481 + 0.242x, R2 = 0.544). The average general fertility rate for the ten-year period was 41.1 live births per 1000 women of the fertile period and ranged from 38.2‰ to 41.7‰. The largest increase in the fertility rate was registered in the age group 40-44 years from 3.8‰ in 2007 to 9.9‰ in 2016 (2.6 times more), and then in the age group 30-39 years with 43.2‰ in 2007 to 63.0 ‰ in 2016 (1.4 times more). There came to a decline in the fertility rate at the age of 20-29 from 80.4‰ in 2007 to 72.2 ‰ in 2016. The highest rates of stillbirth were registered in the oldest group of 45-49 years (23.3 ‰), and the lowest in persons younger than 15 years (0.7‰).Conclusion: Birth revitalization policies must engage all levels of society to build awareness and moral responsibility for fertility.
Keywords: Descriptive study, fertility, trend